Students’ Perception on Pre-Reading Activities in Reading For Gist - Aena Mardiah Putri; Sri Supeni (STIBA IEC JAKARTA, 2024)
Reading is an essential thing in English language skills. To support reading skills, it is necessary to have introductory activities before reading the texts in a classroom (pre-reading activities). Pre-reading activities are necessary to help students understand the reading texts. Reading difficulties can arise if it is not accompanied by a positive perception of pre-reading activities. Therefore, this study will aim to find out the various types of pre-reading activities in the Reading for Gist class and students' perceptions of these activities. This study uses qualitative methods with interviews and questionnaires as the tools of collecting data. The participants in this study were 39 students who took Reading for Gist class. The results of this study show that there are four types of pre-reading activities in Reading for Gist class. The perception given by most students in that class is positive. Students feel that the pre-reading activities are very helpful for them in improving their reading skills.